2014
DOI: 10.1177/1535370214537746
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents LYRM1-induced insulin resistance in 3T3-L1 adipocytes via a mitochondrial-dependent mechanism

Abstract: We previously proposed that LYR motif containing 1 (LYRM1)-induced mitochondrial reactive oxygen species (ROS) production contributes to obesity-related insulin resistance. Metformin inhibits ROS production and promotes mitochondrial biogenesis in specific tissues. We assessed the effects of metformin on insulin resistance in LYRM1-over-expressing 3T3-L1 adipocytes. Metformin enhanced basal and insulin-stimulated glucose uptake and GLUT4 translocation, reduced IRS-1 and Akt phosphorylation and ROS levels, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
(139 reference statements)
2
5
0
Order By: Relevance
“…Interestingly, the supply of lipoic acid had a positive effect on insulin-dependent signaling in L6 myotubes [ 72 ] and ameliorated the negative effects induced by LYRM1 overexpression [ 73 ]. A similar outcome was observed for the anti-diabetic drug, Metformin [ 74 ], which is also an inhibitor of respiratory complex I [ 75 ]. Overall, these results suggest that LYRM1 takes part in a metabolic redox-dependent signaling pathway connected to mitochondrial biogenesis and homeostasis (PI3K, Akt/PKB pathway).…”
Section: The Diverse Roles Of the Lyr Motif Proteins In Mitochondrsupporting
confidence: 73%
“…Interestingly, the supply of lipoic acid had a positive effect on insulin-dependent signaling in L6 myotubes [ 72 ] and ameliorated the negative effects induced by LYRM1 overexpression [ 73 ]. A similar outcome was observed for the anti-diabetic drug, Metformin [ 74 ], which is also an inhibitor of respiratory complex I [ 75 ]. Overall, these results suggest that LYRM1 takes part in a metabolic redox-dependent signaling pathway connected to mitochondrial biogenesis and homeostasis (PI3K, Akt/PKB pathway).…”
Section: The Diverse Roles Of the Lyr Motif Proteins In Mitochondrsupporting
confidence: 73%
“…Exercise-induced PGC1α plays a crucial role in the regulation of muscle metabolism and stimulates the release of METRNL from skeletal muscle 6 . AMPK stimulates PGC1α-mediated signaling 18 , 19 . PGC1α has previously been shown to exhibit powerful suppressive effects on inflammation 20 and insulin resistance 21 .…”
Section: Resultsmentioning
confidence: 99%
“…35 Studies have shown that drugs such as resveratrol, metformin and tetramethylpyrazine all target SIRT1 to increase mitochondrial biogenesis through PGC-1α-dependent pathways. [36][37][38] Further investigations by Ham PB and Price NL have revealed the essential role of resveratrol in mediating AMPK to stimulate SITR1 and induce mitochondrial biogenesis. Resveratrol could increase the activities of cAMP, AMPK and NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1‐mediated mitochondrial biogenesis plays an important role in disease progression 35 . Studies have shown that drugs such as resveratrol, metformin and tetramethylpyrazine all target SIRT1 to increase mitochondrial biogenesis through PGC‐1α‐dependent pathways 36–38 . Further investigations by Ham PB and Price NL have revealed the essential role of resveratrol in mediating AMPK to stimulate SITR1 and induce mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%